Analysis Of Narrative Element (Plot): Case Study Of 5 Short Stories In English From American Literature Website - Siahaan, Sanggam; Tindaon, Cinta Yulistra; Lumbanraja, Theodora Evita Bella; Budiarti, Rika (Universitas Pahlawan Tuanku Tambusai, 2024)
The aim of this research is to conduct an analysis in the form of a case study of 5 short English stories from the American Literature Website. This research employs a qualitative approach, aiming to provide a rich description and insightful explanation and unfold through the collection of plot data, the classification of the plot data, the detailed description and elucidation, and the formulation of conclusions drawn from the insights gained from plot of stories. The research results show that among the five English short stories analyzed, four (80%) exhibit normal progressive plots, while one (20%) presents a distinctive deviation from this norm. Stories 1, 3, and 5 are crafted with normal progressive plots, ensuring a coherent sequence including exposition, trigger action, escalating action, climax, descending action, final action, resolution, and closing. Story 5 also uses a normal progressive plot, only it does not contain descending action, final action, and closing. In contrast, story 2 presents a divergent progressive plot, creating disjointed sequences and unnecessary repetition that may lead to confusion for readers who do not engage with the text attentively.